PENGARUH SOSIALISASI, PENGETAHUAN PERPAJAKAN DAN KETEGASAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DENGAN KUALITAS PELAYANAN PERPAJAKAN SEBAGAI VARIABEL INTERVENING - Sinthya Agustiani; Mohamad Husni; Muhammad Angga Anggriawan (National Conference on Applied Business, Education, & Technology (NCABET), 2022)
This study aims to determine the effect of socialization, knowledge of taxation, firmness of tax sanctions on taxpayer compliance with tax service quality as an intervening variable at KPP Pratama Serang Barat WPOP registered in 2017-2021. The sample selection using a questionnaire survey method with the slovin formula obtained 100 respondents. The tool used in this research is using SmartPLS version 3.0. The results of this study indicate that the socialization variable has no direct effect, but socialization has an influence on the intervening variable. The tax knowledge variable has an influence on the intervening variable and has a direct effect. The tax sanction firmness variable has no direct effect on taxpayer compliance but does affect taxpayer compliance through the intervening variable